Adverse Ocular Impact and Emerging Therapeutic Potential of Cannabis and Cannabinoids: A Narrative Review - Bondok M; Nguyen AXL; Lando L; Wu AY (Clinical Ophthalmology)
Mostafa Bondok,1 Anne Xuan-Lan Nguyen,2 Leonardo Lando,3 Albert Y Wu4 1Department of Medicine, Faculty of Medicine, University of British Columbia, Vancouver, BC, Canada; 2Department of Ophthalmology and Visual Sciences, University of Toronto, Toronto, ONT, Canada; 3Ocular Oncology Service, Barretos Cancer Hospital, Barretos, Brazil; 4Department of Ophthalmology, Stanford University School of Medicine, Stanford, CA, USACorrespondence: Albert Y Wu, Department of Ophthalmology, Stanford University School of Medicine, Stanford, CA, USA, Email awu1@stanford.eduAbstract: Cannabis is the most used drug worldwide with an estimated 219 million users. This narrative review aims to explore the adverse effects and therapeutic applications of cannabis and cannabinoids on the eye, given its growing clinical and non-clinical uses. The current literature reports several adverse ocular effects of cannabis and cannabinoids, including eyelid tremor, ptosis, reduced corneal endothelial cell density, dry eyes, red eyes, and neuro-retinal dysfunction. Cannabinoids may transiently impair night vision, depth perception, binocular and monocular contrast sensitivity, and dynamic visual acuity. Cannabinoids are not currently considered a first-line treatment option for any ocular conditions. Δ-9-tetrahydrocannabinol been shown to result in short-term intraocular pressure reduction, but insufficient evidence to support its use in treating glaucoma exists. Potential therapeutic applications of cannabinoids include their use as a second-line agent for treatment-refractory blepharospasm, for dry eye disease given corneal anti-inflammatory properties, and for suppression of pendular nystagmus in individuals with multiple sclerosis, which all necessitate further research for informed clinical practices.Keywords: cannabis, cannabinoids, adverse effects, therapeutic uses, eye